Recession: A Conceptual Case Study Of Its Domino Effect On Economic And Psychological Capital - Romica Bhat; Prithu Sarkar (Indonesian Journal of Management Studies, 2024)
In this paper, the study will try to understand the conceptual framework of recession through its economic philosophy, psychology, and its narratives on society and livelihood. The behavioral pattern of a recession can be based on many variables like assets, credit volume, unemployment, etc. but these also can be the effect of a recession rather than the cause of the recession. Prediction of the severity of a recession is still a far-fetched concept as experts are still finding it difficult to unfold the formula of the accurate forecast of the same. The word recession itself has a domino sequel on all aspects of functional, execution, and consumption-oriented stakeholders of any country.